Produksi Infused Water Berbahan Dasar Seledri untuk Para Penderita Hipertensi - Muzakar Muzakar; Nathasa Weisdania Sihite; Ahmad Sadiq (Universitas Muhammadiyah Yogyakarta, 2022)
Hypertension is one of the causes of premature death worldwide or better known as the “silent killer,” because people with hypertension often do not feel any symptoms. The prevalence of hypertension in the community is included in the high category, which is 34.1%. The general purpose of this community service is to improve the knowledge and skills of nutrition alumni who are members of IKAGIZI. The specific goal is to foster an entrepreneurial spirit by producing infused water as a functional food product made from celery. These efforts can have health and economic value for the community. Programs and activities are carried out through training and practice in making celery-based infused water products. The service produced commercial functional food products and was expected to be the main solution to reducing hypertension in the community.